Sinergi Nilai-Nilai Islam dan Pendidikan Lingkungan Hidup dalam Pembelajaran Bahasa Inggris: Studi Kasus di SMA Insan Kamil Bogor - Ratu Dinny Fauziah; Rika Rostiany; Neni Yuningsih (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the synergy between Islamic values, Environmental Education (EE), and English Language Learning at Insan Kamil High School in Bogor. Using a mixed methods approach with a sequential explanatory design, data were collected through quantitative assessment of case study text projects by tenth-grade students, which were then explored further through semi-structured interviews and classroom observations (qualitative). The results of the study show a high level of integrative literacy with an average score of 82.2%, where Islamic values such as Khalifah and Mizan play a major moral role in understanding ecological issues. English language learning serves as a means of global articulation that allows students to communicate local environmental wisdom from an Islamic theological perspective. Qualitative findings reveal that the “Eco-Theology Scaffolding” strategy applied by teachers effectively bridges linguistic competence with spiritual awareness. This study concludes that this tripartite integration successfully shapes a globally literate and ecologically sensitive “Eco-Muslim” identity. This model has important implications for the development of interdisciplinary curricula in Islamic educational institutions to address the challenges of global sustainability in the 21st century.